Multi-component bioresponsive nanoparticles for synchronous delivery of docetaxel and TUBB3 siRNA to lung cancer cells. Issue 26 (23rd June 2021) - Conte, Claudia; Monteiro, Patrícia F.; Gurnani, Pratik; Stolnik, Snow; Ungaro, Francesca; Quaglia, Fabiana; Clarke, Philip; Grabowska, Anna; Kavallaris, Maria; Alexander, Cameron
Abstract : Redox-responsive NPs, delivering DTX in combination with TUBB3 siRNA, increased DTX activity in lung cancer (LC) cells. After local administration in LC mice models, NPs were retained into the lungs thus exerting high siRNA silencing efficacy. Abstract : Bioresponsive nanoparticles (NPs) are of interest for anticancer nanomedicines, owing to the possibility to 'design in' selective modulation of drug release at target sites. Here we describe the double emulsion formulation of redox-responsive NPs based on modified polyethylene glycol (PEG)- co -poly(lactic- co -glycolic acid) (PLGA) block copolymers and oligo (β-aminoesters) (OBAE), both of which contained disulfide linkages, for the co-delivery of a cytotoxic small molecule drug and a nucleic acid. In particular, we focused our attention on docetaxel (DTX) and a siRNA against TUBB3, a gene that encodes for βIII-tubulin, in order to have a synergistic effect in the treatment of lung cancer. Spherical NPs of around 150 nm with negative zeta potential and high loading efficiencies of both drugs were obtained. Stability and release studies showed "on demand" drug release under reducing conditions. Unloaded NPs containing PEG-disulfide-PLGA and OBAE were well-tolerated by lung cancer cells, thus masking the intrinsic cytotoxicity of OBAE, while for intracellular siRNA delivery, redox responsive NPs demonstrated a higher cell internalization with a preferential cytoplasmic accumulation of siRNA, with a subsequent fast gene-silencing efficiency. The viability of cells treated with combined DTX/ TUBB3 -siRNA NPs significantly decreased as compared to NPs loaded only with DTX, thus showing an efficient combined anticancer effect, due to a substantial reduction of β-tubulin expression. Finally, in an in vivo feasibility study employing an orthotopic lung cancer model, NPs formulated with an anti-luciferase siRNA distributed throughout the lungs following oro-tracheal administration, and demonstrated effective gene knockdown and no apparent cytotoxicity. Taken together, these results show that the double emulsion formulated redox responsive PEG-PLGA and OBAE systems represent a promising new therapeutic approach for the local combined chemo- and gene-therapy of lung cancer.